2017
DOI: 10.1186/s12864-017-4034-6
|View full text |Cite
|
Sign up to set email alerts
|

AvBD1 nucleotide polymorphisms, peptide antimicrobial activities and microbial colonisation of the broiler chicken gut

Abstract: BackgroundThe importance of poultry as a global source of protein underpins the chicken genome and associated SNP data as key tools in selecting and breeding healthy robust birds with improved disease resistance. SNPs affecting host peptides involved in the innate defences tend to be rare, but three non-synonymous SNPs in the avian β-defensin (AvBD1) gene encoding the variant peptides NYH, SSY and NYY were identified that segregated specifically to three lines of commercial broiler chickens Line X (LX), Line Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In the present study, the expression of associated HDPs showed a significant increase in the cecum of E. tenella infected chickens. HDP in the gastrointestinal tract of chickens are mainly expressed by enterocytes and Paneth cells, and play crucial roles in controlling microbiota and protecting from the pathogenic bacteria in the gastrointestinal tract of chickens 52,53 . CATH, an important HDP in chicken, not only has rapid antimicrobial activity against a broad range of bacteria, but also regulates the immune responses of host cells 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the expression of associated HDPs showed a significant increase in the cecum of E. tenella infected chickens. HDP in the gastrointestinal tract of chickens are mainly expressed by enterocytes and Paneth cells, and play crucial roles in controlling microbiota and protecting from the pathogenic bacteria in the gastrointestinal tract of chickens 52,53 . CATH, an important HDP in chicken, not only has rapid antimicrobial activity against a broad range of bacteria, but also regulates the immune responses of host cells 24 .…”
Section: Discussionmentioning
confidence: 99%
“…HDP in the gastrointestinal tract of chickens are mainly expressed by enterocytes and Paneth cells, and play crucial roles in controlling microbiota and protecting from the pathogenic bacteria in the gastrointestinal tract of chickens. 52,53 CATH, an important HDP in chicken, not only has rapid antimicrobial activity against a broad range of bacteria, but also regulates the immune responses of host cells. 24 However, studies on CATH activity against protozoa, especially E. tenella, are lacking.…”
Section: Changes In Hdp Gene Expression In the Caecum Of E Tenella-in...mentioning
confidence: 99%
“…The decrease in the gene expression may lead to changes in innate immunity and modification of the intestinal microbiota. As a consequence, this may lead to an increase in the host’s susceptibility to disease [ 57 ]. In the expression analysis, we showed that in group 2, where the minerals in the feed and the halloysite were added to the litter, the expression increased numerically.…”
Section: Discussionmentioning
confidence: 99%